Direct evidence of the low-temperature cluster-glass magnetic state of Nd2/3Ca1/3MnO3 perovskite: Магнетизм - Feher, Alexander; Desnenko, Vladimir; Fertman, Elena; Dolya, Sergiy; Kajňaková, Marcela; Beznosov, Anatoly (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
In the presented study we have revealed a giant exchange bias in a colossal magnetoresistance Nd2/3Ca1/3MnO3 perovskite at low temperatures, evident of an intrinsic exchange coupling in this compound. The phenomena found confirms our previous assumption that the low-temperature magnetic structure of the compound is represented by small (nanosized) ferromagnetic clusters immersed within the charge-ordered antiferromagnetic matrix. Magnetic behavior of the Nd2/3Ca1/3MnO3 perovskite is consistent with a cluster-glass magnetic state and does not agree with a classical spin-glass state observed in a variety of disordered magnetic systems. We think that the cluster-glass magnetic behavior of Nd2/3Ca1/3MnO3 originates from the selforganized phase-separated state of the compound. The Cole-Cole analysis of the dynamic susceptibility at lowtemperatures has shown extremely broad distribution of relaxation times, indicating that spins are frozen at a “macroscopic” time scale. Slow relaxation of the zero-field-cooled magnetization has been experimentally revealed as well. This slow relaxation confirms the cluster-glass magnetic state of the compound. Two strongly different relaxation mechanisms were found: the first one is characteristic for temperatures below the freezing temperature Tg 60 K, the second one is characteristic for higher temperatures.